LANGUAGE BARRIERS IN VERTICAL COMMUNICATION WITHIN THE MULTINATIONAL CORPORATION - Dar, Asim Ijaz (My University, 2010)
Purpose – The Purpose of this study is to provide a better understanding of the language related issues and its impact on communication between HQ and subsidiaries in a Scandinavian MNC. Design/methodology/approach – The research is based on a qualitative in-depth single case study. The empirical data was collected through semi-structured interviews from the company, Lyreco. The theoretical framework was constructed by taking into consideration all the solutions and some mediating factors such as time and distance. Findings – It was found that language acts as an important barrier between HQ and subsidiaries, slowing down the communication process. However, the study highlights that these were not only language differences that caused a barrier but also cultural differences. At the same time, language policies also have their influence on the functioning of multinationals. In addition; the research suggests some solutions to deal with language barriers. However, each solution has a combination of advantages and disadvantages, and no certain solution can be considered as a perfect one to deal with the language barriers. MNCs thus need to understand the language barriers well and mix and match the solutions into a blend that is right for the company context. Research limitations – This study was confined to a single case study. The results might therefore have more value if the data sample had been larger or with multiple case companies. Originality/value –The study highlights the crucial role of the language in international business and draws attention to the potential for communication problems arising from the language diversity.
Keywords: Vertical Communication; Language; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|